How the earth got its beauty - Murty, Sudha (Gurugram; Puffin Books, 2021)
After the huge successof How the Sea Became Salty and How the Onion Got ItsLayers, Sudha Murty brings to you a brand new tale aspart of her gorgeous chapter book series for young readers. Excellent artwork that helps expand a child's imagination, easy to read and understand. A remarkable story narrated simply and endearingly for young readers. Have you ever stopped to marvel at the earth's beauty: at snow-capped mountains and oceans so deep; at colourful flowers and extraordinary animals? The tale of how such beauty came into existence is a curious one indeed.
Keywords: Children's stories; Fiction